Seven-coordinate iron complex as a ditopic receptor for lithium salts: Study of host-guest interactions and substitution behavior - Sarauli, David; Popova, Vesselina; Zahl, Achim; Puchta, Ralph; Ivanovic-Burmazovic, Ivana (Inorganic Chemistry, 2007)
Interactions between the seven-coordinate tweezerlike [Fe(dapsox)(H O)]ClO complex (Hdapsox = 2,6-diacetylpyridine-bis(semioxamazide)) with different lithium salts (LiOTf, LiClO, LiBF, and LiPF) in CHCN have been investigated by electrochemical, spectrophotometric, Li and F NMR, kinetic, and DFT methods. It has been demonstrated that this complex acts as ditopic receptor, showing spectral and electrochemical ion-pair-sensing capability for different lithium salts. In general, the apparent binding constants for lithium salts increase in the order LiOTf < LiClO < LiBF. From the electrochemical measurements, the apparent lithium salt binding constants for the Fe(III) and Fe(II) forms of the complex have been obtained, suggesting a stronger host-guest interaction with the reduced form of the complex. In the presence of LiPF, the solution chemistry is more complex because of the hydrolysis of PF . The kinetics of the complexation of [Fe(dapsox)(CHCN)] by thiocyanate at -15°C in acetonitrile in the presence of 0.2 M NBuOTf shows two steps with the following rate constants and activation parameters: k = 411 ± 14 M s; ΔH = 9 ± 2 kJ mol; ΔS = -159 ± 6 J K mol; k = 52 ± 1 M s; ΔH = 4 ± 1 kJ mol; ΔS = -195 ± 3 J K mol. The very negative ΔS values are consistent with an associative (A) mechanism. Under the same conditions but with 0.2 M LiOTf, k and k are 1605 ± 51 and 106 ± 2 M s respectively. The increased rate constants for the [Fe(dapsox)(CHCN)]-LiOTf adduct are in agreement with an associative mechanism. Kinetic and spectrophotometric titration measurements show stronger interaction between the lithium salt and the anion-substituted forms, [Fe(dapsox)(CHCN)(NCS)] and [Fe(dapsox)(NCS)], of the complex. These experiments demonstrate that in nonaqueous media lithium salts cannot be simply used as supporting electrolytes, since they can affect the kinetic behavior of the studied complex. DFT calculations revealed that the negatively charged α-oxyazine oxygen atoms are responsible for cation binding (electrostatic interactions), whereas the two terminal amide groups bind the anion via hydrogen bonding. © 2007 American Chemical Society.